2011
DOI: 10.1007/s10532-011-9494-9
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of three pharmaceutical active compounds by the fungus Phanerochaete chrysosporium in a fed batch stirred reactor under air and oxygen supply

Abstract: White-rot fungi are a group of microorganisms capable of degrading xenobiotic compounds, such as polycyclic aromatic hydrocarbons or synthetic dyes, by means of the action of extracellular oxidative enzymes secreted during secondary metabolism. In this study, the transformation of three anti-inflammatory drugs: diclofenac, ibuprofen and naproxen were carried out by pellets of Phanerochaete chrysosporium in fed-batch bioreactors operating under continuous air supply or periodic pulsation of oxygen. The performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 41 publications
0
53
0
2
Order By: Relevance
“…Metabolites formed via fungal transformation suggested that hydroxylation was catalyzed by monooxygenases cooperating with cytochrome P-450. However, the authors did not exclude the role of extracellular ligninolytic enzymes in diclofenac transformation (90 % during 3 days) (Hata et al 2010;Rodarte-Morales et al 2012). The same metabolites were indicated in a culture of bacteria-Actinoplanes sp.…”
Section: Microbial Degradation/transformation Of Diclofenacmentioning
confidence: 94%
“…Metabolites formed via fungal transformation suggested that hydroxylation was catalyzed by monooxygenases cooperating with cytochrome P-450. However, the authors did not exclude the role of extracellular ligninolytic enzymes in diclofenac transformation (90 % during 3 days) (Hata et al 2010;Rodarte-Morales et al 2012). The same metabolites were indicated in a culture of bacteria-Actinoplanes sp.…”
Section: Microbial Degradation/transformation Of Diclofenacmentioning
confidence: 94%
“…Performance of WRF for PhAC removal has been predominantly assessed under sterile conditions to avoid bacterial contamination [158,165,166]. This is because bacterial contamination under non-sterile conditions can negatively affect the performance of whole-cell WRF [154,167].…”
Section: White-rot Fungi and Their Extracellular Enzymesmentioning
confidence: 99%
“…Some degradative potential was also found in white-rot fungi such as Trametes versicolor, Irpex lacteus, Ganoderma lucidum, Phanerochaete chrysosporium, Bjerkandera adusta and Bjerkandera sp. R1 (Marco-Urrea et al 2009, Rodarte-Morales et al 2012. Studies on activated sludge show that even a complex consortium of microorganisms is characterized by low effi ciency of ibuprofen degradation (Quintana et al 2005).…”
Section: Introductionmentioning
confidence: 99%